Treatment Patterns and Clinical Outcomes in Patients With Metastatic Gastroenteropancreatic Neuroendocrine Tumors Treated in the Community Practice Setting in the United States. Issue 2 (February 2018) - Jiao, Xiaolong; Pulgar, Sonia; Boyd, Marley; Braiteh, Fadi; Mirakhur, Beloo; Pitman Lowenthal, Susan; Fox, Patricia; Frytak, Jennifer; Cox, David; Paulson, A. Scott
Abstract : Objective: This study was conducted to understand treatment patterns and clinical outcomes in metastatic gastroenteropancreatic neuroendocrine tumor patients treated in a large community oncology network. Methods: This retrospective study used the McKesson Specialty Health/US Oncology Network iKnowMed electronic health record database with supplemental chart review. Eligibility criteria included a metastatic neuroendocrine tumor diagnosis between January 1, 2008, and to December 31, 2012; at least 2 US Oncology Network visits; and age at least 18 years. Follow-up was through October 31, 2014. Results: Among the 229 patients identified, median age was 64.0 years, 52.4% were male, 69.4% were white, and 62.9% were overweight/obese. Primary tumor sites included small bowel (47.6%), pancreas (31.4%), and stomach/colorectum (21.0%). There were 16.2% under observation without treatment, 52.4% received only somatostatin analogs (SSAs), and 31.4% received chemotherapy/targeted therapy during treatment. In the first-line setting (n = 192), 77% received SSAs, 12% received chemotherapy, and 10.9% received targeted therapy. Fifty percent of patients receiving octreotide had a relative dose intensity of less than 85%, and 16.7% received above-label dose. Toxicities of SSAs included diarrhea (18.2%), abdominal pain (16.9%), and fatigue (13.5%). Median overall survival from diagnosis was 68.0 months (95% confidence interval, 57.1 to not reached). Conclusions: Most metastatic gastroenteropancreatic neuroendocrine tumor patients received systemic treatment with SSAs. Patient treatment used an individualized dosing approach. Overall survival and toxicity were consistent with the published literature.